Case report of chloroquine therapy and hypoglycaemia in type 1 diabetes: What should we have in mind during the COVID-19 pandemic? (2020)
A type 1 diabetes patient experienced remission associated with chloroquine therapy while travelling to a malaria-endemic area. Chloroquine has immunomodulatory and hypoglycaemic effects and may become more frequently used due to the COVID-19 pandemic. Patients with type 1 diabetes treated with chloroquine should be monitored for hypoglycaemia, even after recovery.